The Positive Impact of University-Community Engagement Projects: A Case Study in the Context of Universiti Malaya - Hasan, Siti Idayu; Abu Bakar, Azizi; Mat Radi, Nor Azlin; Mansor, Muhammad Asyraf; Hamzah, Zalfa Laili; Amer Nordin, Amer Siddiq (Journal of Research Management and Governance, 2023)
Collaborative partnership or engagement between university and community are essential and have become a widespread practice adopted by many universities worldwide. While university-community-engagement projects which are undertaken in a variety of ways of multidiscipline are growing rapidly, questions about its impact on communities remain largely ignored. Little empirical evidence is available exploring the impact of such partnerships for either the community partners or the university. This study presents a case study of the Universiti Malaya’s experience of evaluating the impact of such engagements through several funded community projects. These university-community engagement funding are disbursed and managed by UM’s Community Engagement Centre (UMCares). The result chain model was applied to collect data on the input, activities, output, outcomes and impact of the funded projects. Differences in nine impact areas and indicators were also identified. The results show that the funding projects are able to create an impact in different areas of community engagement. However, the development and maintenance of a dedicated database, in combination with periodic, systematic impact assessments is crucial to increase impact in community engagement.